Exploitation, vulnerability, and the body: a philosophical examination of commercial surrogacy - Barn, G (2017)
Since its inception, surrogacy has generated substantial debate in the philosophical literature. India has been host to a lucrative transnational surrogacy industry, where Indian women of low socioeconomic status serve as surrogates for predominantly wealthy foreigners. This thesis examines whether Indian commercial surrogacy is typically exploitative, and what, if anything, follows from this. I develop and defend a working account of exploitation focused on the unfair use of vulnerability: A exploits B when A takes unfair advantage of B’s vulnerability. I define vulnerability according to a conception of justice, endorsing the capabilities approach as a working definition, due to the way in which it is able to reflect the plurality of disadvantage, and coheres particularly well with the experience of Indian surrogates. I bring this definition of exploitation to bear on the Indian surrogacy industry, suggesting that the situation therein constitutes wrongful exploitation. I argue that Indian surrogacy is typically ex ante harmfully exploitative according to Alan Wertheimer’s influential definition, and therefore merits intervention by his own lights. Following this, I consider what remains wrongful about mutually advantageous exploitation, if the element of harm were to be removed. I give three arguments for intervening in wrongful exploitation in the absence of such harm. First, I make a consequentialist argument, suggesting that in light of exploitation’s suboptimal nature as a mode of exchange, arguments for permitting mutually advantageous exploitation actually turn out to fall short in their welfarist aims, and intervention into exploitation plausibly produces better long term consequences. Following this, I make a non-consequentialist argument focusing on use of vulnerability, and the unfair advantage this generates. The use of vulnerability in this way is wrongful insofar as it trades on an objectionable and rectifiable injustice, and inflicts a status harm on the vulnerable, rendering exploitation inimical to ideals of relational equality. My third and final argument for intervention into mutually advantageous exploitation employs Clare Chambers' social constructivist approach, suggesting that when a "free choice" is influenced by prior injustice, and results in further disadvantage, there are reasons to intervene. Lastly, I suggest that the embodiment aspect of the nature of the labour in transactions such as surrogacy make them of special concern, and the exploitation of this type of labour particularly pernicious.